Farmer to Farmer Extension Approach to increase Coffee Farmers' Food Security - Andi Warnaen; Nurlaili Nurlaili; Yastutik Yastutik (Department of Agribusiness, Faculty of Agriculture, Universitas Trunojoyo Madura, Indonesi, 2022)
The purpose of this study was to determine what factors influence the food security of coffee farmers, primarily through the Farmer-to-Farmer approach (or independent extension officer) and formulate a model of food security for coffee farmer families. This approach uses a quantitative approach with survey research methods. The research was conducted in Malang Regency, East Java Province, especially in the Districts of Ampelgading, Sumbermanjing Wetan, Trirtoyudo and Dampit. This study's population was 2,622 coffee farmers with a total sample size of 96 people selected using the Propositional random sampling technique. Data were analyzed using Structural Equation Modeling (SEM) based on the variant Generalized structured component analysis (GSCA). The results showed that the Family Farmers' Food Security was more dominantly influenced by independent Extension Officers' Role. Meanwhile, the role of independent extension officers is more dominantly influenced by the role of civil servant extension officers. The conclusion of this study is to increase the role of Independent Extension Workers in increasing the food security of coffee farmers. It is necessary to increase the role of independent extension officer, especially in providing consultation to farmers.